Pengaruh Pemberian Edukasi terhadap Tingkat Kecemasan dan Mean Arterial Pressure (MAP) Pasien Pre Anestesi untuk Tindakan Sectio Caesarea di RSUD Dr. SOEDIRMAN KEBUMEN - Febby Febrian Denni; Rahmaya Nova Handayani; Etika Dewi Cahyaningrum (Malahayati Nursing Journal, 2025)
ABSTRACT Sectio Caesarea is a major surgical procedure that often causes anxiety in patients. Pre-anesthesia anxiety can affect hemodynamic conditions, including blood pressure and Mean Arterial Pressure (MAP). Pre-anesthesia education is believed to be able to reduce anxiety and stabilize the patient's physiological condition. One method used is education through video media. Objectives: (1) to identify the level of anxiety before and after education in pre-anesthesia Sectio Caesarea patients at Dr. Soedirman Hospital, Kebumen, (2) to identify MAP values before and after education, (3) to analyze the effect of education on anxiety levels, and (4) to analyze the effect of education on MAP values. Methods: This study used a pre-experimental one group pretest-posttest design with a sample of 45 patients undergoing Sectio Caesarea. The study was conducted for 1 month on March 14-April 12, 2025, with a population of 101 patients. The instruments used were the APAIS questionnaire to measure anxiety and a blood pressure measuring instrument to calculate MAP. Data analysis using the Wilcoxon test. Results The average anxiety value from 60% experiencing severe anxiety to 64.4% experiencing mild anxiety and the Map value from 105 to 90 the study showed a significant decrease in the level of anxiety P value 0.000 and MAP P value 0.000 after education (p 0.05). Conclusion: Pre-anesthesia education through video media is effective in reducing anxiety levels and stabilizing MAP values in pre-anesthesia patients with Sectio Caesarea. This education is recommended to be part of the standard of pre-anesthesia services in hospitals. Keywords: Education, Anxiety, MAP, Pre-Anesthesia, Sectio Caesarea  ABSTRAK Sectio caesarea merupakan tindakan pembedahan mayor yang sering menimbulkan kecemasan pada pasien. Kecemasan pre-anestesi dapat memengaruhi kondisi hemodinamik, termasuk tekanan darah dan Mean Arterial Pressure (MAP). Edukasi pra-anestesi dipercaya mampu menurunkan kecemasan serta menstabilkan kondisi fisiologis pasien. Salah satu metode yang digunakan adalah edukasi melalui media video. Tujuan: (1) mengidentifikasi tingkat kecemasan sebelum dan sesudah edukasi pada pasien pre-anestesi Sectio Caesarea di RSUD Dr. Soedirman Kebumen, (2) mengidentifikasi nilai MAP sebelum dan sesudah edukasi, (3) menganalisis pengaruh edukasi terhadap tingkat kecemasan, dan (4) menganalisis pengaruh edukasi terhadap nilai MAP. Metode: Penelitian ini menggunakan desain pre-eksperimental one group pretest-posttest dengan sampel sebanyak 45 pasien yang menjalani Sectio Caesarea. Penelitian dilakukan selama 1 bulan pada tanggal 14 Maret-12 April 2025, dengan jumlah Populasi sebanyak 101 paisen. Instrumen yang digunakan adalah kuesioner APAIS untuk mengukur kecemasan dan alat ukur tekanan darah untuk menghitung MAP. Analisis data menggunakan uji Wilcoxon. Hasil Nilai rata-rata kecemasan dari 60% mengalami kecemasan berat menjadi 64.4 % mengalami kecemasan ringan dan nilai Map dari 105 menjadi 90 penelitian menunjukkan adanya penurunan yang signifikan pada tingkat kecemasan P value 0.000 dan MAP P value 0.000 setelah pemberian edukasi (p 0,05). Kesimpulan: Edukasi pra-anestesi melalui media video efektif menurunkan tingkat kecemasan dan menstabilkan nilai MAP pada pasien pre-anestesi Sectio Caesarea. Edukasi ini disarankan menjadi bagian dari standar pelayanan pra anestesi di rumah sakit. Kata Kunci: Edukasi, Kecemasan, MAP, Pre Anestesi, Sectio Caesarea